Markers of Bone Turnover Predict Postmenopausal Forearm Bone Loss Over 4 Years: The OFELY Study - Patrick Garnero; Elisabeth Sornay‐Rendu; F. Duboeuf; Pierre D. Delmas (1999)
The ability of biochemical markers to predict the rate of postmenopausal bone loss is still controversial. To investigate this issue further, baseline levels of a panel of specific and sensitive biochemical bone markers were correlated to the rate of change of forearm bone mineral density (BMD) assessed by four measurements over a 4-year period using dual-energy X-ray absorptiometry in a large population-based prospective cohort of 305 women aged 50-88 years (mean 64 years), 1-38 years postmenopausal. In the whole population, higher baseline levels of bone formation (serum osteocalcin and serum type I collagen N-terminal propeptide) and bone resorption markers (urinary N-telopeptides; urinary and serum C-telopeptides) were significantly associated with faster BMD loss (r = -0.19 to -0.30, p < 0.001), independently of age. In women within 5 years of menopause that have the highest rate of bone loss, the predictive value of bone markers was increased with correlation coefficients reaching 0.53. Women with an abnormally high bone turnover, i.e., with levels of bone markers at baseline 2 SD above the mean of premenopausal women, had a rate of bone loss that was 2- to 6-fold higher than women with a low turnover (p = 0.01-0.0001) according to the marker. When the population was categorized according to quartiles of bone markers at baseline, a similar relationship between increased levels of bone markers and faster rate of bone loss was found (p = 0.008-0.0001). In the logistic regression model, the odds-ratio of fast bone loss, defined as the rate of bone loss in the upper tertile of the population, was increased by 1.8- to 3.2-fold for levels of biochemical markers in the high turnover group compared with levels within the premenopausal range, with, however, a limited value for identifying individual fast bone losers. We conclude that increased levels of some of the new biochemical markers of bone turnover are associated with greater radial bone loss. Because increased bone loss is associated with an increased risk of fracture, bone turnover markers may be useful to improve the prediction of the risk of osteoporosis in postmenopausal women.